2020
DOI: 10.3390/ijms21093079
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Modulates Dendritic Architecture in a BDNF-Dependent Manner

Abstract: The brain-derived neurotrophic factor (BDNF) plays crucial roles in both the developing and mature brain. Moreover, alterations in BDNF levels are correlated with the cognitive impairment observed in several neurological diseases. Among the different therapeutic strategies developed to improve endogenous BDNF levels is the administration of the BDNF-inducing drug Fingolimod, an agonist of the sphingosine-1-phosphate receptor. Fingolimod treatment was shown to rescue diverse symptoms associated with several neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…In patients with MS, treatment with fingolimod significantly increased BDNF secretion from T cells, suggesting that neuroprotective effects of fingolimod therapy are through BDNF enhancement ( Golan et al, 2019 ). Fingolimod regulates dendritic architecture and morphology of healthy mature primary hippocampal neurons alongside BDNF dependent enhancement in c-Fos and pERK1/2 proteins ( Patnaik et al, 2020 ). We have recently shown that BDNF enhancement by fingolimod correlates with upregulation in oligodendrocyte mRNA levels in the EPI-NCSCs ( Pournajaf et al, 2020 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with MS, treatment with fingolimod significantly increased BDNF secretion from T cells, suggesting that neuroprotective effects of fingolimod therapy are through BDNF enhancement ( Golan et al, 2019 ). Fingolimod regulates dendritic architecture and morphology of healthy mature primary hippocampal neurons alongside BDNF dependent enhancement in c-Fos and pERK1/2 proteins ( Patnaik et al, 2020 ). We have recently shown that BDNF enhancement by fingolimod correlates with upregulation in oligodendrocyte mRNA levels in the EPI-NCSCs ( Pournajaf et al, 2020 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In 2013, Doi and others found that fingolimod-P can suppress Amyloid β–induced neurotoxicity in primary mouse cortical neurons by enhancing BDNF expression and acting on TrkB/ERK1/2 signaling pathway ( Doi et al, 2013 ). Recently, it has been shown that with the aid of BDNF, 10 nM fingolimod can modulate dysregulated dendritic architecture in primary hippocampal neurons ( Patnaik et al, 2020 ). Moreover, fingolimod can downregulate AD’s neuroinflammation by reducing activated microglia, astrocytosis, and plaque density ( Aytan et al, 2016 ; Kartalou et al, 2020 ).…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling neurons and subsequent morphological reconstruction of the neurons provides information about the dendrite morphometric and axonal properties that are crucial for network establishment. These properties can give valuable insight in large scale disease modeling and drug testing screens ( DePoy et al, 2014 ; Miguéns et al, 2015 ; Cheng et al, 2017 ; Martínez-Cerdeño, 2017 ; Patnaik et al, 2020 ). Much is yet to be understood as to how human neuron morphology is driven in 3D brain in vitro models where all connectivity pathways are miniaturized.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological reconstruction of the neurons provides information about the dendrite morphometric and axonal properties that are crucial for network establishment. These properties can give valuable insight in large scale disease modelling and drug testing screens 2,3 . Much is yet to be understood as to how human neuron morphology is driven in brain organoids where all connectivity pathways are miniaturized.…”
Section: Introductionmentioning
confidence: 99%